(untitled) (Colombia Medica, 1993)
A teaching-learning program for self-care was applied to a group of people attending the Centro Día del Anciana/o San Miguel de Cali, Colombia. The knowledge obtained and how it was applied in the number and quality of self-care activities was measured. A quasi-experimental design was used with an equal number of people in the experimental and control groups distributed in randomized blocks by age and sex. A biopsychosocial survey and scales to measure functional capacity and/or intellectual function were used to characterize the sample. A knowledge test was applied before and after the teaching-learning program to the experimental group, and a checklist to measure self-care activities performed by the experimental and control groups. The data on knowledge obtained before and after the program and the self-care activities in the experimental group were compared with those of the control group. Significant differences were found in both cases. It is concluded that the elderly learn and apply self-care that contributes to their well-being. Nursing professionals have a determining role in the development of educational programs for self-care